Endothelial Dysfunction in a Bitch: Treatment with Superficial Keratectomy Combined with Conjunctival Advancement of the “Gundersen” and Modified “Gundersen” Types - Aguiar da Silva, Kamila; Chaves Guberman, Úrsula; Gomes Rocha, Thaís; dos Santos Honsho, Cristiane (Acta Scientiae Veterinariae, 2025)
Background: Endothelial dysfunction affects small and elderly dogs and is similar to Fuchs’ corneal endothelial dystrophy observed in humans. This condition can be hereditary or acquired and is progressive, potentially leading to corneal edema, bullous keratopathy and recurrent, indolent ulcers. The aim of this report is to describe a case of bilateral endothelial dysfunction treated by a superficial lamellar keratectomy followed by conjunctival advancement using both Gundersen and modified Gundersen techniques in a 8-year-old bitch Shih-tzu with corneal ulcer refractory to clinical treatment, and to describe the 17-month postoperative outcome. Case: A 8-year-old bitch Shih-tzu was referred for ophthalmological evaluation due to progressive ocular opacity without blindness, developed over 2 months. The patient was using an Elizabethan collar and was being treated for bilateral superficial corneal ulcers with antibiotic eye drops and lubricating gel. Ophthalmological examination revealed moderate mucous secretion and normal menace response, normal pupillary light reflexes (direct, consensual and dazzle). Both eyes presented corneal edema, more pronounced in the right eye. Tear production and intraocular pressure were normal, and bilateral superficial ulcers were noted in the paracentral region. The patient was diagnosed with endothelial dysfunction and bilateral corneal ulcers, and treatment with antibiotic and hyperosmotic eye drops, oral analgesics and maintenance of the protective collar was initiated. After 14 days, ocular secretion improved, but edema and ulceration persisted in both eyes. Dimethylpolysiloxane-based eye drops were added, and due to the low therapeutic response, bilateral conjunctival advancement using the Gundersen technique was recommended for the left eye and the modified Gundersen technique for the right eye, where corneal edema was more intense. The conjunctival flaps were sutured with monofilament nylon in a simple interrupted and continuous pattern and were removed after 31 days. During this period, antibiotic, hyperosmotic and lubricating eye drops were continued. Oral anti-inflammatory and analgesic medications were also administered. Four days postoperatively, with ulcer resolution in the left eye, prednisolone-based eye drops were added, and the same was done for the right eye on the 22nd day. On the 37th day postoperatively, antibiotic and anti-inflammatory eye drops were discontinued, maintaining the hyperosmotic agent and lubricant, and adding the topical immunomodulator. After 6 months, the owner reported clearer eyes with no signs of discomfort, ocular secretion, or tearing. In the follow-up, 17 months postoperatively, the dog had been off all medication for 3 months. Positive menace responses and movement tests were observed; bilateral ocular opacity and corneal pigmentation in the left eye were noted, with no episodes of corneal ulcer since the procedure. Discussion: Endothelial dystrophy has been reported in dogs of various breeds, including Shih-tzu. There is a greater predisposition in bitches and elderly dogs, as seen in this case. With the decline in endothelial function, the remaining cells are unable to maintain deturgescence, allowing fluid accumulation between the collagen lamellae, causing corneal thickening, loss of transparency, development of keratopathies and blindness secondary to edema. Corneal ulcers frequently recur in patients with endothelial dysfunction, are challenging to heal, and cause ocular discomfort and corneal pigmentation. Among the therapeutic options, superficial keratectomy combined with conjunctival advancement is an easily performed procedure that does not require donors, and offers the potential to reduce edema, the recurrence of corneal ulcers, and discomfort. Keywords: dog, ophthalmology, cornea, corneal ulcers, edema, conjunctival edema.